Point-based tree representation: A new approach for large hierarchies - Hans-Jörg Schulz; Steffen Hadlak; Heidrun Schumann (PacificVis'09: Proceedings of the IEEE Pacific Visualization Symposium, 2009)
Space-filling layout techniques for tree representations are frequently used when the available screen space is small or the data set is large. In this paper, we propose a new approach to space-filling tree representations, which uses mechanisms from the point-based rendering paradigm. Additionally, helpful interaction techniques that tie in with our layout are presented. We will relate our new technique to established space-filling techniques along the lines of a newly developed classification and also evaluate it numerically using the measures of the Ink-Paper-Ratio and overplotted%.